Habilidad gerencial y desempeño de mercado: una investigación de empresas que cotizan en B3 - Poffo, Rubia Frehner (2025)
Companies continuously seek strategies to enhance their market performance. Among the factors that may influence this performance, the managerial ability with which executives carry out their responsibilities stands out. In this context, the present study aims to examine whether more ability managers contribute to improved market performance among Brazilian firms. Ability managers tend to analyze organizational information more carefully, which provides them with superior predictive capabilities (Bessy et al., 2024; Hasan, 2018). This attribute supports more effective and efficient decision-making, positively impacting business outcomes (Fagundes et al., 2024; Ribeiro & Souza, 2023; Wang et al., 2017). The study employed a sample of 206 firms covering the period from 2019 to 2023. The analysis was conducted using ordinary least squares (OLS) regression with fixed effects for industry and year, utilizing the Stata® software. The results indicate that more capable managers are associated with superior market performance, reinforcing the assumptions of the resource-based view. Managerial capabilities such as identifying relevant information, anticipating changes in the external environment, and strategically analyzing the organizational landscape are internal resources that firms should leverage to enhance their competitiveness. Thus, this research contributes to the literature by highlighting the role of managerial capabilities as drivers of market performance.